Intervenciones de enfermería en el control prenatal en gestantes con preeclampsia en el primer nivel de atención. - Chimborazo Llamuca, Blanca del Pilar (2025)
Preeclampsia is a complication that impacts maternal and neonatal health. This complication could be avoided if women received guidance, prenatal care with timely interventions, and effective follow-up for prevention and treatment. Predisposing risk factors include a lack of professional care during pregnancy and prenatal surveillance. Objective: To describe nursing interventions during prenatal care in pregnant women with preeclampsia at the primary care level. Methodology: A comprehensive literature search was conducted in recognized scientific databases. Articles published in the last 5 years were included. Twenty-six documents published in indexed journals were selected: Pubmed 5, Lilacs 4, Dialnet 3, Scielo 20, Elsevier 2, and Redalyc. Results: The theoretical foundations of approaches that support comprehensive nursing care for pregnant women with preeclampsia were identified. Clinical approaches included strict monitoring of vital parameters and risk classification. The psychological aspect is the reduction of anxiety and strengthening of the mother-child bond; the educational aspect is information on self- care, warning signs, and treatment adherence; the cultural aspect is communication and adaptation, respecting knowledge, beliefs, and practices; and the community aspect is the active participation of the family and stakeholders in their context. Conclusions: The analysis has demonstrated the importance of trained nurses and interventions in prenatal care for pregnant women with preeclampsia, with and without severe signs, at the primary care level. Early detection, provision of health services, and appropriate, coordinated management of preeclampsia are essential to prevent serious complications for both mother and fetus.